2017
DOI: 10.1016/j.molstruc.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions directed assembly of two coordination polymers based on an organic phosphonate anion and a multidentate N-donor ligand

Abstract: Two new coordination polymers [Cd(4,4'-tmbpt)(HL)(H 2 O)] (1) and [Cu(4,4'-tmbpt)(HL)]•H 2 O (2) (H 3 L = 2'-carboxybiphenyl-4-ylmethylphosphonic and 4,4'-tmbpt = 1-((1H-1,2,4-triazol-1-yl)methyl)-3,5-bis(4-pyridyl)-1,2,4-triazole) have been synthesized hydrothermally. The two compounds have the same metal to ligand ratio, but different metal ions. As a result, the two compounds display different 2D layer structures, which is mainly caused by the different coordination numbers of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…On the other hand, Kan et al have synthesized MOFs of Cu(II) and Cd(II) by using mixed ligands consisting of phosphonate, carboxylate, and triazine moieties. 144 These phosphonate-based Cu/Cd-MOFs showed good photocatalytic activity in the decomposition of pollutant organic dyes due to photoactive (low band gap) ligand species in their frameworks. Thompson and co-workers have utilized the phosphonate group of the polymer surfactant for stabilizing Pt nanocolloids over Zr(IV) viologen-phosphonate material, and it showed excellent catalytic activity in photocatalytic hydrogen generation.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kan et al have synthesized MOFs of Cu(II) and Cd(II) by using mixed ligands consisting of phosphonate, carboxylate, and triazine moieties. 144 These phosphonate-based Cu/Cd-MOFs showed good photocatalytic activity in the decomposition of pollutant organic dyes due to photoactive (low band gap) ligand species in their frameworks. Thompson and co-workers have utilized the phosphonate group of the polymer surfactant for stabilizing Pt nanocolloids over Zr(IV) viologen-phosphonate material, and it showed excellent catalytic activity in photocatalytic hydrogen generation.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…In an alternative approach, Yuan et al have reported porous titania–phosphonate materials through postsynthetic functionalization of TiO 2 surfaces with bridging organophosphorous precursor tetra- and penta-phosphonates, and the resulting organic–inorganic hybrid materials showed high photocatalytic efficiency in the decomposition of the organic dye Rhodamine B in the presence of UV or visible light irradiation. On the other hand, Kan et al have synthesized MOFs of Cu­(II) and Cd­(II) by using mixed ligands consisting of phosphonate, carboxylate, and triazine moieties . These phosphonate-based Cu/Cd-MOFs showed good photocatalytic activity in the decomposition of pollutant organic dyes due to photoactive (low band gap) ligand species in their frameworks.…”
Section: Applications Of Porous Metal Phosphates and Phosphonatesmentioning
confidence: 99%